THE REGIONAL FACTOR IN THE SURGICAL TREATMENT OF BREAST CANCER - Aviño, J. (2015)
The results obtained from 95 patients who underwent breast cancer during the biennium 1983-1985, by type of intervention performed analyzes. In most patients they have undergone a modified PATEY, following the HALSTED number and a simple mastectomy, more cleaning axillary The lymph nodes was classified into 3 levels or stages. Our approach is to keep the pectoralis major long as it is not affected by the tumor and removal of the pectoralis minor, for better subclavian surgical time.